Strategy The principal's Leadership Style in Implementing “Merdeka Belajar” in Schools - Mastur Mastur (Universitas Kristen Satya Wacana, 2023)
Curriculum changes are part of improving the existing education system in Indonesia. Principal leadership has an important role and position in achieving educational goals. This study aims to discuss the principal's leadership style in implementing